Making walking and cycling safer. Lessons from Europe. - Pucher, John; Dijkstra, Lewis (My University, 2000)
The neglect of pedestrian and bicycling safety in the United States has made these modes dangerous ways of getting around. Pedestrian fatalities are 36 times higher than car occupant fatalities per km traveled, and bicycling fatalities are 11 times higher than car occupant fatalities per km. Walking and bicycling can be made quite safe, however, as clearly shown by the much lower fatality rates in The Netherlands and Germany. Pedestrian fatalities per billion km walked are less than a tenth as high as in the United States, and bicyclist fatalities per billion km cycled are only a fourth as high. The Netherlands and Germany have long recognized the importance of pedestrian and bicyclist safety. Over the past two decades, these countries have undertaken a wide range of measures to improve safety: better facilities for walking and bicycling; urban design sensitive to the needs of non-motorists; traffic calming of residential neighborhoods; restrictions on motor vehicle use in cities; rigorous traffic educationof both motorists and nonmotorists; and strict enforcement of traffic regulations protecting pedestrians and bicyclists. The United States could adopt many of the same measures to improve pedestrian and bicycling safety here. The necessary technology and methods are already available, with decades of successful experience in Europe. difu
Keywords: Fahrradverkehr; Fußgängerverkehr; Verkehrssicherheit; Verkehrsunfall; Verkehrsberuhigung; Verkehrsplanung; Verkehrsmittelwahl; Verkehrsverhalten; Mobilität; Verkehrspolitik; Verkehrsfläche; Siedlungsfläche; Individualverkehr; Fahrradnutzung; Radverkehrsanteil; Fahrradförderung; Nichtmotorisierter Verkehr